Efektifitas Penerapan Aplikasi Perlintasan Keimigrasian (APK) di Tempat Pemeriksaan Imigrasi (TPI) Bandara Internasional I Gusti Ngurah Rai- Bali - Ignatius Willy Rimaldo Lodang; Benyamin Tunga; Luh Nila Winarni; Cokorde Istri Dian Laksmi Dewi (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The purpose of this study was to determine the effectiveness of the application of the Immigration Crossing Application (APK) and to know the obstacles encountered in the application of the Immigration Crossing Application (APK) at the Immigration Checkpoint (TPI) of I Gusti Ngurah Rai International Airport - Bali. The application of this APK is a product of the Directorate General of Immigration as an effort to implement Law No 6 of 2011 concerning Immigration. The immigration function as regulated in Law No 6 of 2011 covers immigration services, law enforcement, state security and development facilitators. Methodology: This type of research is research with an empirical juridical approach. Data collection techniques using interview methods and other data collection as needed. The data obtained were analyzed descriptively qualitatively. The results obtained are: 1). Application of APK at TPI International Airport I Gusti Ngurah Rai- Bali has not been effective 2). The obstacles faced in implementing APK at I Gusti Ngurah Rai International Airport Bali are the unstable electrical system at I Gusti Ngurah Rai International Airport - Bali which causes component damage to the server device (APK) owned by TPI I Gusti International Airport Ngurah Rai-Bali and the lack of immigration officers, especially landing officials on duty at each counter at the TPI Ngurah Rai-Bali International Airport and this application has not detected data on someone's crossing if entering through TPI I Gusti Ngurah Rai International Airport - Bali and exiting through TPI Airport Soekarno Hatta and 3). The efforts that have been made to date in overcoming obstacles to the application of the Immigration Crossing Application (APK) at the Immigration Checkpoint (TPI) I Gusti Ngrah Rai International Airport - Bali do not yet exist. Results: The results of this study are academically beneficial for various parties while immigration officials can be used as a reference in conducting further research as an evaluation material for improving policies and as a reference for making other policies.